AN ANALYSIS OF CODE SWITCHING USED BY AN ENGLISH TEACHER OF SMA NEGERI 1 TAMBUSAI - Wahyuni Lestary; Erni Erni; Supriusman Supriusman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: English is a foreign language in Indonesia. English is important because it is the international language. During classroom activities, teachers and students switched from English to Indonesian and other local languages. This research aims to analyze code- collected using an observation checklist and recording to gather the data in the use of code switching used by an English teacher of SMA Negeri 1 Tambusai. This research used qualitative research method with descriptive qualitative. The data for this research were switching in the classroom. The subject of the study is the English teacher of the twelfth grade students. After collecting the data, the data were analyzed through some steps namely data reduction, data display and conclusion drawing. The result of this research showed there are two types of code switching used by an English teacher of SMA Negeri 1 Tambusai. The most common types which occurred in teacher’s utterance are situational code-switching with nine data, the second common type which is metaphorical code-switching with one data. There are two forms of code switching used by English teacher. The most common form which occurred in teacher’s utterance is internal code-switching with sixteen data and then the second common form is external code-switching with ten data.Key Words: Code-Switching, Descriptive Qualitative Method, English Teaching Process.